2011
DOI: 10.4248/ijos11052
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor prevalence has an impact on the constituent ratio of metastases to the jaw but not on metastatic sites

Abstract: This article provides an overview of metastases to jaws (MJ), mainly concerning the differences between American and Chinese patients, and exploring the relationship between the primary tumors' prevalence (PTP) and constituent ratio of MJ. Information concerning of 399 MJ cases in 215 papers, including one new case in our hospital, was subjected to statistic analysis. The main clinical features of MJ, such as constituent ratio of PTP and that of MJ, metastatic sites, treatments, and prognosis were summarized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
6
0
2
Order By: Relevance
“… 2,3 The ramus and the molar region are the favoured metastatic sites in the mandibular bone. Zhang et al 3 suggested that good vascularization of the jaw bone increased the risk of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“… 2,3 The ramus and the molar region are the favoured metastatic sites in the mandibular bone. Zhang et al 3 suggested that good vascularization of the jaw bone increased the risk of metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Çene kemiğine metastaz yapan primer tümör alanları temelde meme, akciğer, böbrek, prostat ve tiroid bezidir. [6] Bu nedenle hastamızın geçmişinde meme kanseri öyküsü olması nedeniyle lezyonun öncelikle metastatik olabileceği düşünülerek PET-BT incelemesi yapıldı. Biyopsi ve cerrahi yöntemle alınan örneğin histopatolojik incelemesi sonucu meme karsinomu metastazı ile uyumlu olmayan hastanın PET-BT incelemesinde de ek patoloji saptanmayınca metastatik hastalık olasılığı ekarte edildi.…”
Section: Discussionunclassified
“…The latest studies were included in the analyses to avoid double citation. In addition, two extensive series were not included since they did not meet the study criteria and it was impossible to identify whether their series included solely lung carcinomas in their series [7,8]. The collected data was added to the data published in M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT the previous study in which the literature was searched from 1916 to 2006 [6].…”
Section: Introductionmentioning
confidence: 99%